Omni-channel integration: the matter of information and digital technology - Saghiri, Soroosh; Mirzabeiki, Vahid (Emerald, 2021)
This paper aims to explore how omni-channel data flows should be integrated by specifying what data, omni-channel agents and information and digital technologies (IDTs) should be considered and connected. Design/methodology/approach A multiple case study method is used with 17 British companies. The studies are supported by 68 interviews with the case companies and their consumers, 5 site visits, 4 focus group meetings and the companies’ archival data and documentations. Findings This paper provides novel frameworks for omni-channel data flow integration from consumer and business perspectives. The frameworks consist of omni-channel agents, their data transactions and their supporting IDTs. Relatedly, this paper formalizes the omni-channel data flow integration in the forms of horizontal, vertical and total integrations and explores their contributions to the adaptability of omni-channel, as a complex adaptive system (CAS). It also discusses that how inter-organizational governance mechanisms can support data flow integration and their relevant IDT implementations. Research limitations/implications The breadth and depth of the required IDTs for omni-channel integration prove the necessity for omni-channel systems to move toward total integration. Therefore, supported by CAS and inter-organizational governance theories, this research indicates how data flow integration and IDT can transform the omni-channel through self-organization and autonomy capability enhancement. Originality/value This research’s recommended frameworks provide a robust platform to formalize data flow integration as the omni-channel's core driver. Accordingly, it moves the literature from a basic description of “what omni-channel is” and provides a novel and significant debate on what specific data should be shared at what levels between which agents of the omni-channel, and with what type of relationship governance mechanism, to assure omni-channel horizontal, vertical and total integrations.
Keywords: Omni-channel; Data flow integration; Information and Digital Technology (IDT); Complex Adaptive System; Inter-organizational governance